A Pragmatic Analysis of Deixis on Song Lyrics “Espresso” By Sabrina Carpenter - Nazula, Aizzatul; Prasetyo, Yudy; Sabat, Yuliyanto (ITScience (Information Technology and Science), 2026)
Pragmatics studies how meaning is understood in context, and deixis is an important part of it because it connects language with person, time, place, discourse, and social relationships. Song lyrics contain many context dependent expressions, so they are suitable for pragmatic analysis. This study aims to identify the types of deixis and explain their contextual meanings in the song “Espresso” by Sabrina Carpenter. This study used a descriptive qualitative method. The data were taken from the song lyrics and consisted of words, phrases, and sentences that contain deixis expressions. The analysis was based on the theories of Yule (1996) and Levinson (1983), who classify deixis into person, time, place, social, and discourse deixis. The results show that all five types of deixis appear in the song. Person deixis is the most dominant type, especially the use of I and you, which shows interaction between the singer and the addressee and highlights the singer’s identity. Time deixis explains when events happen, while place deixis describes movement and direction that support the lively tone of the lyrics. Social deixis shows closeness through terms of address, and discourse deixis connects ideas in the lyrics to make the message coherent. These findings show that deixis in song lyrics does not only function as reference but also expresses identity, emotions, and interpersonal relationships. This study helps readers understand how contextual meaning is built in popular song lyrics from a pragmatic perspective and shows the role of language in shaping meaning in music.